1987
DOI: 10.1099/00221287-133-8-2197
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cAMP Level in the Yeast Saccharomyces cerevisiae: the Glucose-induced cAMP Signal Is Not Mediated by a Transient Drop in the Intracellular pH

Abstract: Addition of glucose to derepressed cells of the yeast Saccharomyces cerevisiae is known to cause a rapid, transient increase in the cAMP level, which lasts for 1-2min and induces a CAMPdependent protein phosphorylation cascade. The glucose-induced cAMP signal cannot be explained solely on the basis of an increased ATP level. Transient membrane depolarization and transient intracellular acidification have been suggested as possible triggers for the cAMP peak. Addition of glucose to cells in which the plasma mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 9 publications
0
53
0
Order By: Relevance
“…A small decrease of the ATP levels was observed within the first minute of glucose readdition, followed by slow restoration of the intracellular ATP pool between 5 and 20 min (Table 3). A transient and rapid drop of ATP levels within 30 s of glucose addition to glucose-derepressed yeast cells has been previously detected by 31 P nuclear magnetic resonance spectroscopy and attributed to formation of sugar phosphates (63). As shown in Table 3, following glucose addition, yeast cells showed kinetics of ATP recovery almost indistinguishable from kinetics for the recovery in YEP, although the mechanism of recovery is almost certainly different.…”
Section: Resultsmentioning
confidence: 78%
“…A small decrease of the ATP levels was observed within the first minute of glucose readdition, followed by slow restoration of the intracellular ATP pool between 5 and 20 min (Table 3). A transient and rapid drop of ATP levels within 30 s of glucose addition to glucose-derepressed yeast cells has been previously detected by 31 P nuclear magnetic resonance spectroscopy and attributed to formation of sugar phosphates (63). As shown in Table 3, following glucose addition, yeast cells showed kinetics of ATP recovery almost indistinguishable from kinetics for the recovery in YEP, although the mechanism of recovery is almost certainly different.…”
Section: Resultsmentioning
confidence: 78%
“…At first, rather unspecific mechanisms such as transient plasma membrane depolarization (23,31) and transient intracellular acidification (10,36,46) were proposed. However, these hypotheses were shown to be wrong, and other rather unspecific mechanisms, such as increased energy supply, were also excluded (17,41,42). On the other hand, it was confirmed that drastic lowering of the intracellular pH in yeast cells strongly stimulates in vivo cAMP synthesis (41).…”
mentioning
confidence: 64%
“…(23,31) and transient intracellular acidification (10,36,46) were proposed. However, these hypotheses were shown to be wrong, and other rather unspecific mechanisms, such as increased energy supply, were also excluded (17,41,42 …”
mentioning
confidence: 99%
“…Cell extracts were prepared as previously described by Thevelein et al (1987) with the following modifications: cells were harvested by filtration and cAMP was extracted with 1 ml 15 % perchloric acid with three freeze-thaw cycles in liquid nitrogen. After centrifugation, the supernatant was neutralized by 1?5 M potassium carbonate/1 M acetic acid buffer.…”
Section: This Work Ol641-40bmentioning
confidence: 99%